An Unusual Case of Bleeding in Small Intestine - Miroslav Vujasinovic; Martin Måhl; Carmen Mesas Burgos; Cecilia K. Zetterström; Denis Nastic; Gabriele Wurm Johansson; Ervin Toth (Turkish Journal of Gastroenterology, 2021)
Cite this article as: Vujasinovic M, Mahl M, Mesas Burgos C, et al. An unusual case of bleeding in small intestine. Turk J Gastroenterol. 2021; 32(7): 608-610.